Organochlorine pesticides and PCBs in Southern Right Whales (Eubalaena australis) breeding at Península Valdés, Argentina - Torres, Pablo Javier (2015)
Organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) were assessed in blubber from 35 dead Southern Right Whales (SRW — Eubalaena australis) stranded at Península Valdés, Argentina. The life cycle includes a feeding period in high productivity areas of the South West Atlantic and a reproductive period in coastal template waters of Argentina. Organochlorine pesticides showed higher concentrations (22.6 ± 13.8 ng·g− 1 ww) than PCBs (7.5 ± 10 ng·g− 1 ww). Among pesticides, HCHs, DDTs, endosulfans, dieldrin, chlordans, heptachlor epoxide, and trans-nonachlor were detected. p,p′-DDE and p,p′-DDT were present in 69% and 26% of samples, respectively. p,p′-DDT/p,p′-DDE ratio showed low values (< 0.33) as a result of aged DDT inputs. However, the occurrence of only p,p′-DDT in some samples suggests a recent pesticide input. α-HCH/γ-HCH ratio (< DL-0.37) indicated no recent contribution of technical HCH mixture and/or current use of lindane. Dieldrin was present in 77% of the samples and endosulfan was detected in all samples with predominance of α- (75%) over β-endosulfan (19%) and scarce contribution of endosulfan sulphate (7%), suggesting a recent input of this insecticide to the environment in the SRW foraging area. A predominance of pentachlorobiphenyls was observed. In 21 samples at least one PCB indicator was found and PCB #118, highly toxic, contributed in 5% to total PCBs. Although all these organochlorine compounds are forbidden they were bioaccumulated in the blubber of SRW with a predominance of endosulfans, the more recently used pesticide. The absence of data on chemical pollutants in stranded dead whales is highlighted as a priority for research. This is the first study on levels, compositional patterns, and organochlorine sources in SRW. Moreover, more research including milk, and other tissues/organs is recommended considered that in the studied specimens, mostly calves, pollutants are likely transferred from the mother during pregnancy and nursing.